Comparison of Safety between Different Kinds of Heparins in Patients Receiving Intra-Aortic Balloon Counterpulsation - Guan, Xiaonan; Chen, Mulei; Li, Yanbing; Zhang, Jianjun; Xu, Li; Sun, Hao; Zhang, Dapeng; Wang, Lefeng; Yang, Xinchun (The Thoracic and Cardiovascular Surgeon, 2020)
Background The present study aimed to compare the effectiveness and safety of low molecular-weight-heparin (LMWH) and unfractionated heparin (UFH) in acute myocardial infarction (AMI) patients receiving intra-aortic balloon counterpulsation (IABP).Materials and Methods We retrospectively analyzed a total of 344 patients receiving IABP for cardiogenic shock, severe heart failure, ventricular septal rupture, or mitral valve prolapse due to AMI. A total of 161 patients received UFH (a bolus injection 70 U/kg immediately after IABP, followed by infusion at a rate of 15 U/kg/hour and titration to for 50 to 70 seconds of activated partial thromboplastin time. A total of 183 patients received LMWH (subcutaneous injection of 1.0 mg/kg every 12 hours for 5 to 7 days and 1.0 mg/kg every 24 hours thereafter). Events of ischemia, arterial thrombosis or embolism, and bleeding during IABP were evaluated. Major bleeding was defined as a hemoglobin decrease by >50 g/L (vs. prior to IABP) or bleeding that caused hemodynamic shock or life-threatening or requiring blood transfusion.Results Subjects receiving UFH and LMWH did not differ in baseline characteristics. Ischemia was noted in five (3.1%) and two (1.1%) subjects in UFH and LMWH groups, respectively. Arterial thromboembolism occurred in three (1.9%) subjects in the UFH group, but not in the LMWH group. Logistic regression analysis failed to reveal an association between ischemia or bleeding with heparin type. Major bleeding occurred in 16 (9.9%) and six (3.3%) patients in the UFH and LWMH groups, respectively (p = 0.014). Regression analysis indicated that LMWH is associated with less major bleeding.Conclusion LMWH could reduce the risk of major bleeding in patients receiving IABP. Whether LMWH could reduce arterial thromboembolism needs further investigation.
Keywords: low-molecular-weight heparin; unfractionated heparin; acute myocardial infarction; intra-aortic balloon counterpulsation